Eficiencia de mercado: un estudio empírico en otros países seleccionad - Mongrut, Samuel (2002)
This paper surveys three methods for testing the weak form of market efficiency: the autocorrelation coefficient, the variance ratio, and the lead-on-the-lag regression. All of them have different strengths and limitations, so they provide complementary insights about market efficiency. The three methods are applied to a sample of eleven countries and to the world stock index. The results reveal the appearance of market anomalies in capital markets, specifically overreaction and mean reversion, with differences in timing and duration. These differences could be due to cross-country differences in investment horizons among investors.